Efficacy of ankle Kinesio taping on balance and functional performance in obese female collegiate students: a prospective randomized placebo-controlled trial - Allam, Nesma M.; Eladl, Hadaya Mosaad; Elsherbini, Dalia Mahmoud Abdelmonem; Abulfaraj, Moaz; Almadani, Moneer E.; Megahed Ibrahim, Ateya; El-Sherbiny, Mohamed; Eladl, Mohamed A.; Nosseir, Nermine; Jamjoom, Reda (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to evaluate the efficacy of ankle Kinesio taping (KT) on static and dynamic balance and functional performance in obese female collegiate students.DesignThis study was a prospective, randomized controlled trial.SettingThe research was conducted in outpatient physical therapy settings.ParticipantsA total of 40 female collegiate students, aged 18–25 years, were randomly assigned to two groups of equal size.InterventionGroup A (KT group) received KT with 75–100% tension, and group B (Placebo KT group) received placebo KT with 0% tension. KT was applied to the dominant leg in both groups for 6 weeks.Outcome measuresThe primary outcome was static balance, which was measured using the single-leg stance test (SLST). The secondary outcomes were dynamic balance, assessed using the Biodex Balance System (BBS), and functional performance, which was assessed using the single-leg vertical jump test (SLVJT) and single-leg hop test (SLHT). All outcomes were assessed at baseline and after 6 weeks.ResultsThe KT group showed a statistically significant increase in SLS, SLVJT, and SLHT (p < 0.001), compared to the placebo KT group. In contrast, a statistically significant decrease was observed in the OSI, MLSI, and APSI (p < 0.001) in the KT group compared to the control group after a period of 6 weeks.ConclusionThe application of a 6-week KT mechanical correction technique can improve static and dynamic balance and functional performance in obese female university students compared to the placebo group. Including KT in the treatment plan is recommended for obese women with balance and functional performance deficits.Clinical trial registrationClinicalTrials.gov, identifier NCT06195748.